A quest to upgrade first generation universities in Nigeria to produce innovative and ICT-ready health educators (2013)
The importance of health education in today’s society has been extensively researched and discussed. As professionals of an independent discipline collaborating with other members of the health care team, health educators perform a specific and vital function for which they must be carefully trained. The place of creativity and innovation towards making health educators responsive to societal yearnings is enormous. This article identifies innovation driven competencies required of health educators in the execution of their tasks. It also attempts a thorough critique of the deficiencies of first generation universities in Nigeria towards equipping prospective health education graduates enter the profession able to apply theory to practice. Equipped to be result oriented, innovation driven and poised to surmount the myriads of challenges posed by the uniqueness of this technological advancement. The article also explored critical steps towards re-tooling and re-positioning first generation universities in Nigeria from the student service paradigm to the student development paradigm with the aim of meeting the health information challenges of the Nigerian society. In conclusion, first- generation universities must create new health educational tools and strengthen existing curricula, modules and courses. They must break with tradition and find innovative ways of performing their uniquely valuable functions and exploring all possible means to produce health education graduates that are responsive to societal needs.